BABESIOSIS IN HUMANS - Zornitsa Traykova (Problems of Infectious and Parasitic Diseases)
Babesiosis is a tick-borne parasitic disease caused by the intraerythrocytic protozoan Babesia spp. and transmitted primarily by Ixodes ticks. The geographical distribution of the parasites coincides with the regions where their tick vectors are prevalent. More than 50 cases of human babesiosis have been reported in Europe, mainly associated with Babesia divergens, which causes acute disease in cattle and is transmitted by Ixodes ricinus. In contrast, the incidence of the disease in the USA is approximately 2000 cases per year, with the main causative agent being Babesia microti and the tick vector being Ixodes scapularis. Although babesiosis is primarily an animal disease, humans can also become acutely ill, particularly splenectomized and immunocompromised individuals. Clinical manifestations range from asymptomatic to severe disease with symptoms including fever, chills, hemoglobinuria and anemia. There is a risk of potentially fatal complications such as acute respiratory, renal or multi-organ failure, particularly in vulnerable populations. Diagnosis is primarily based on light microscopy and PCR testing, while serological methods are more appropriate for epidemiological studies. Treatment regimens typically include a 7-10 day course of either atovaquone plus azithromycin or clindamycin plus quinine. Human cases are associated with outdoor activities or living in rural areas during the warm months when tick activity is at its peak. Because of the increasing incidence in endemic regions and the potentially serious clinical consequences, babesiosis should be considered in the differential diagnosis of febrile illnesses of unknown origin.